A knockout psychological intervention: The effect of PETTLEP-based imagery on boxing performance - Smith, D.; Wright, C. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Holmes and Collins (2001) developed the PETTLEP model to help practitioners produce functionally equivalent imagery. PETTLEP is an acronym, each letter representing a key issue to consider when implementing imagery interventions: Physical, Environment, Task, Timing, Learning, Emotion and Perspective. Recent studies suggest that PETTLEP-based imagery interventions are more effective than more traditional interventions (Smith, Wright, Allsopp & Westhead, in press). However, it will not always be possible to incorporate all the guidelines into imagery interventions, and therefore information regarding the effects of interventions focusing on different PETTLEP components would be useful. Also, the model still needs to be comprehensively tested with various skills. Therefore, this study examined the effects of interventions focused on the environment and timing components of PETTLEP in boxing. Fifty-two amateur boxers were divided into three groups: An `environment` group, a `timing` group and a control group. Participants performed pre-tests and post-tests consisting of three commonly-used punch combinations against a defensive boxer using pads. A qualified boxing judge scored the punches. Following the pre-test, imagery participants imaged performing the combinations successfully three times per week for six weeks. The timing group imaged at home whilst listening to an audio recording of them performing successful combinations. This recording acted as a template enabling participants to image in `real time` (cf. Smith & Holmes, 2004). The environment group imaged in the boxing ring where testing took place, dressed in their boxing clothing. Controls read boxing literature. A group x test ANOVA for performance scores revealed a significant interaction effect, F (2,45) = 10.67, p<.001. Tukey HSD tests revealed that both imagery groups improved significantly between pre- and post-tests, with the environment group improving to a significantly greater degree than the timing group, but the control group did not improve. These results support the efficacy of interventions focusing on the environment and timing PETTLEP components, and suggest that the environment component is particularly important to obtain optimal results from imagery. Implications for practitioners will be explored, and practical recommendations suggested, regarding the incorporation of these PETTLEP components into imagery interventions.